An energy-efficient virtual machine scheduler with I/O collective mechanism in resource virtualisation environments. (1st January 2013) - Xiao, Peng; Liu, Dongbo
Recently, resource virtualisation has been proven effective for deploying large-scale IT-infrastructures, such as grids and clouds. However, many studies also indicate that the system's energy-efficiency will be reduced when I/O virtualisation is involved. In this paper, we present an energy-efficiency enhanced virtual machine (VM) scheduler with aiming at reducing the energy-efficiency losses caused by I/O virtualisation. The proposed VM scheduler is incorporated with an I/O collective mechanism, which separates I/O-intensive VMs from CPU-intensive ones during the runtime and schedules them in a batch manner, so as to reduce the context-switching costs when scheduling intensive mixed workloads. Extensive experiments are conducted on various platforms by using different benchmarks to investigate the performance of the proposed policy. The experimental results indicate that when the virtualisation platform is in presence of mixed workloads, the proposed scheduler outperforms many existing VM schedulers in term of energy-efficiency.